Qur’an in Conversation: By Michael Birkel (Waco, TX: Baylor University Press, 2014. 282 pages.) (American Journal of Islam and Society, 2016)
This book is meant for non-Muslims who want to understand the Qur’an butare perplexed by it. Describing it as a complex book, neither thematic norchronological, but elliptical with much of its content out of reach of the uninitiated,Michael Birkel explores how it is interpreted among North AmericanMuslims. From the beginning, this non-Muslim author highlights the diversityof approaches and manages to present accessible “insider’s” views. Its sevensections contain a selection of voices obtained through personal interactionwith the twenty-four Muslim contributors, a brief introduction, and a closingconclusion.The first contribution, “The Mother of the Book,” reflects upon how theQur’an’s first chapter is both foundational as its “opening” and opens heartsthroughout each of the five daily prayers. The two partner pieces, “KnowledgeHidden and Manifest,” focus on the Qur’anic accounts of Joseph (by IngridMattson) and the encounter between Moses and the mysterious Khidr (byMaria Dakake). The themes of both stories, namely, faith and wisdom, drawthe reader into the wider theme of aligning oneself with God. The author thenmoves on to his second theme: “Close Readings, Old and New.” MohammadHassan Khalil discusses God’s mercy with the phrase “In the name of God,the Compassionate, the Merciful,” which appears at the beginning of all butone sūrah. He wrestles with the idea of an everlasting hell, having discoveredas a student that some Muslim scholars challenge it on the basis of God’smercy. Alongside this “shocking” (his expression) opinion, he also cameacross the conviction that non-Muslims would receive God’s mercy in theHereafter. Challenging negative readings of the Qur’an, he says, “Readingthe Qur’an under the benevolent shadow of raḥma allows one to appreciateScripture on a different level” (p. 37) ...